2021
DOI: 10.1080/21655979.2021.1997224
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0001879 promotes the progression of atherosclerosis by regulating the proliferation and migration of oxidation of low density lipoprotein (ox-LDL)-induced vascular endothelial cells via the miR-6873-5p-HDAC9 axis

Abstract: Atherosclerosis (AS) is a typical vascular disease. Emerging evidence has shown that circRNAs play key roles in the progression of AS, but the potential function and underlying mechanism of hsa_circ_0001879 remains unknown. We detected the expression level of hsa_circ_0001879 was determined by qRT-PCR, and the proliferation rate and migration ability of HUVECs were measured by CCK-8 assay and Transwell assay, respectively. Proliferative markers and epithelium mesenchymal transition (EMT) markers were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Previous studies indicated that HDAC9 was involved in the pathogenesis of AS. A study reported that HDAC9 participated in the development of AS through modulating cell growth and metastasis of ox‐LDL‐triggered HUVECs 23 . HDAC9 was reported to be involved in aortic calcification of AS, which also could impact cell phenotype of vascular smooth muscle cells 50 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated that HDAC9 was involved in the pathogenesis of AS. A study reported that HDAC9 participated in the development of AS through modulating cell growth and metastasis of ox‐LDL‐triggered HUVECs 23 . HDAC9 was reported to be involved in aortic calcification of AS, which also could impact cell phenotype of vascular smooth muscle cells 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple researches reported that HDAC9 affected several aspects of AS pathogenesis and development, such as interleukin 6 (IL‐6) signaling, platelet aggregation, cholesterol efflux, inflammation progression, and macrophage function 21,22 . Moreover, HDAC9 was revealed to be implicated in regulating the proliferative and migratory abilities of ox‐LDL‐triggered vascular endothelial cells in AS progression, suggesting the regulatory role of HDAC9 in AS 23 . However, whether HDAC9 could act as a downstream gene of ASV to take part in AS development is still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidized low-density lipoprotein (LDL) is a potentially risky type of cholesterol for arterial atherosclerosis that is generated when normal LDL cholesterol is damaged by free radicals and can be taken up by cells through scavenger receptor-mediated endocytosis [ 18 , 19 ]. Interestingly, several studies have reported that oxidized LDL was involved in the EMT process through its receptor interactions to trigger a cascade of the signaling pathway [ 20 , 21 , 22 , 23 ] and specific miRNAs [ 24 ]. Additionally, it has been reported that the elevation of plasma oxidized LDL leads to early fibrosis in not only kidney parenchyma across the whole spectrum of CKD stages [ 25 , 26 , 27 ] but also cardiac myofibroblasts [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above-mentioned issues [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], we tested the hypothesis that oxidized LDL might play an essential role in the deterioration of the residual renal function in setting of CKD through upregulation of renal tubular epithelial cells EMT process and renal fibrotic signaling pathway.…”
Section: Introductionmentioning
confidence: 99%